Beyond cell-cell contact: therapeutic potential of Eph signaling in central nervous system tumors - Ribeiro, Fernanda Cristina Poscai; Gonçalves, Moisés Willian Aparecido; Silva, Aleff Mascarenhas; Maciel, Tayná Figueiredo; de Lima-Souza, Reydson Alcides; Scarini, João Figueira; Fillmore, Gary Chris; Egal, Erika Said Abu (Frontiers in Molecular Neuroscience, 2025)
Eph receptor tyrosine kinases and their membrane-bound ephrin ligands constitute a unique bidirectional signaling system that orchestrates cell adhesion, migration, proliferation, and vascular patterning, processes frequently co-opted in malignancy. We conducted an integrative review of preclinical models and clinical cohorts to delineate Eph/ephrin expression landscapes and evaluate functional outcomes in central nervous system neoplasms. In gliomas, particularly glioblastoma multiforme, overexpression of EphA2 and EphA3 correlates with higher tumor grade and increased invasiveness. Conversely, ephrin-A1 and ephrin-A5 exhibit tumor-suppressive properties by promoting receptor internalization and degradation, thereby inhibiting glioma cell proliferation and migration. In medulloblastoma, elevated expression of EphB1 and EphA4 is associated with enhanced angiogenesis and migratory capacity, contributing to tumor progression. In meningiomas, aberrant activation of EphA2 and EphB1 promotes proliferation through engagement with mTOR and ERBB3 signaling pathways. Emerging therapeutic strategies, including ligand-targeted cytotoxins, selective kinase inhibitors, chimeric antigen receptor T cells, and ephrin-based immunomodulators, demonstrate potent anti-tumor efficacy in preclinical settings, highlighting the translational potential of targeting the Eph/ephrin axis. The dualistic nature of Eph/ephrin signaling underscores its translational promise as both a biomarker framework and a precision-guided therapeutic target. Combinatorial receptor-ligand modulation strategies may advance the treatment of central nervous system malignancies by exploiting the context-dependent roles of Eph/ephrin interactions.